2010
DOI: 10.1099/vir.0.026344-0
|View full text |Cite
|
Sign up to set email alerts
|

Passaging of a Newcastle disease virus pigeon variant in chickens results in selection of viruses with mutations in the polymerase complex enhancing virus replication and virulence

Abstract: Some Newcastle disease virus (NDV) variants isolated from pigeons (pigeon paramyxovirus type 1; PPMV-1) do not show their full virulence potential for domestic chickens but may become virulent upon spread in these animals. In this study we examined the molecular changes responsible for this gain of virulence by passaging a low-pathogenic PPMV-1 isolate in chickens. Complete genome sequencing of virus obtained after 1, 3 and 5 passages showed the increase in virulence was not accompanied by changes in the fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 50 publications
2
48
1
3
Order By: Relevance
“…Sequencing of the whole genome revealed that the increase in virulence of the virus passaged in chickens was not associated with changes in the F protein, but with mutations which occurred in genes encoding L and P proteins. These proteins are responsible for replication of the genome, including the synthesis of RNA strands of positive polarity, which serves as a template for the RNA strand of negative polarity (Dortmans et al 2011). Therefore, the pathogenicity of PPMV-1, and thus the ICPI ratio, is determined not only by the amino acid composition of the F protein, but also by the viral replication complex (proteins NP, P and L) (Dortmans et al 2011).…”
Section: Pathogenicity Of the Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequencing of the whole genome revealed that the increase in virulence of the virus passaged in chickens was not associated with changes in the F protein, but with mutations which occurred in genes encoding L and P proteins. These proteins are responsible for replication of the genome, including the synthesis of RNA strands of positive polarity, which serves as a template for the RNA strand of negative polarity (Dortmans et al 2011). Therefore, the pathogenicity of PPMV-1, and thus the ICPI ratio, is determined not only by the amino acid composition of the F protein, but also by the viral replication complex (proteins NP, P and L) (Dortmans et al 2011).…”
Section: Pathogenicity Of the Virusmentioning
confidence: 99%
“…The complex of proteins NP, P and L is responsible for the transcription and replication of the viral genome. NP protein forms a nucleocapsid enclosing the viral RNA, protein P enables the synthesis of RNA and protein L functions as an RNA-dependent RNA polymerase and is responsible for the post-transcriptional modifications of mRNA (Dortmans et al 2011). HN and F glycoproteins, forming two types of viral surface projection, play a special role in the course of infection and are the major antigens, which cause an immune response.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Rhabdoviridae (Kim et al, 2014), Filoviridae (Ebihara et al, 2006) and Bornaviridae (Ackermann et al, 2007). This Cterminal component of L proteins of NNS RNA viruses, especially the region between domains V and VI, is highly variable, and considered as a domain of L which interacts with unique host cell transacting transcriptional cofactors (Dortmans et al, 2011;Poch et al, 1990;Sidhu et al, 1993). The mutations in guinea pig-lethal MARV L protein, however, affect the domain III close to the GDNQ/E motif, presumably directly modulating the processivity of viral RNA-dependent RNA polymerase (Liang et al, 2015).…”
mentioning
confidence: 99%
“…This was associated with 3 amino acid mutations, 2 in the L protein and 1 in the P. 148 A further study examining all 6 NDV genes showed that whilst the F gene is the main determinant of pathogenicity, the polymerase L gene is the second most important contributor. 120 …”
Section: Viral Replication Complexmentioning
confidence: 99%